Role of interleukin‐6 and pentraxin 3 as an early marker in Peyronie's disease. Issue 4 (28th February 2017) - Atar, Arda; Kural, Alev; Yenice, Gurkan; Comez, Ilker; Tugcu, Volkan
Abstract: Inflammation is mechanistically involved in the development of Peyronie's disease (PD). The aim of this study is to assess the relevance of serum pentraxin 3 (PTX3) and interleukin‐6 (IL‐6) concentrations in PD. The study enrolled 40 patients with PD in the acute phase and 40 healthy controls. Plasma PTX3 and IL‐6 concentrations were evaluated in 40 patients in the acute phase of PD and 40 healthy controls by enzyme‐linked immunosorbent assay. Serum concentrations of both PTX3 and IL‐6 were significantly higher in the PD patients than in the control group ( p = 0.001 and p = 0.001, respectively). There was a significant correlation between concentration of PTX3 and painful erections. IL‐6 concentrations were significantly higher in patients with erectile dysfunction. IL‐6 and PTX3 levels showed no correlation with age, serum C‐reactive protein, degree of curvature, and disease duration. IL‐6 trans‐signaling and PTX3 amplification at the site of inflammation could have a role in pathophysiological mechanisms of PD. Biological drugs may be used for treatment during the acute phase of the disease based on this mechanism.